PERSEPSI PERAN, KONSISTENSI PERAN, DAN KINERJA - Soemanagara1, Rizky Dermawan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
This paper describes the relationship between role perception, role consistency, andperformance. The role consistency is described as a commitment to expected behavior for a given position. The description of the idea of consistency is borrowed from time-consistency theory of economics